TINJAUAN YURIDIS KEBIJAKAN PEMERINTAH KABUPATEN JEMBER TERHADAP EKSPLOITASI GUMUK - Isnania Citra Saisabela; Fauziyah Fauziyah (MIMBAR YUSTITIA, 2017)
In the use of hills in Jember District related land rights, which most hills in Jember District is private property rights and its utilization cannot be contrary with national interests. In the article 6 UUPA : " All rights over land have a social function". Then on the basis of the law of the government Jember could not only dwell alone without a policy on the protection of the hills. With private ownership over the hills cannot be a reason to ignore the sustainability and environmental protection. The process of development and the protection of environment must be in harmony. Not mutual clashing that culminated in the destruction of the environment. The harmony between the use and maintenance of the environment related to the hills should always maintained in order to safeguard environment quality of life as well as the use of hills must be adjusted with the case and th nature of the right to useful both for peace and prosperity that does and useful for the society, state and public interests. Aware of the condition that happens, author regretted government attitude of Jember against Local Regulation of Jember Number 1 Year 2015 About Regional Exterior Plan Jember District 2015 - 2035 inconsistent with implementation to the use hills. With done by people to hills exploitation economic interests, the impact on the environment. if the view is subjective, it is obvious for the perpetrators of such as hills owner, miners, investors, view it give positive impact for open jobs and improve economic mobility in the region. But for people around the hills, will feel mostly negatives impact, as the weather hotter, drought, erosion, flood, high wind, and micro climate change. The hand of the government through all its policies must put the protection and preservation of environment as the main priority. Economic growth must be consistent with the protection of environment. The current generation must be bequeathed to the next generation of good natural. So the utilization of hills can be done by making hills as a green tourism park, place jogging track, place students research with planted with various plants and conservation of flora and fauna and the existence of a over zoning for the protection hills to as one of the efforts the management of environmental sustainability, with create a community care hills and action as the government policy control of Jember related to the protection hills, proposing an objection against the decision officials responsible for development that is not considered in accordance with the spatial plan, working together with the Government in the spatial plan and oversee the implementation of spatial plan.